VATS right upper lobe bronchial sleeve resection - Ma, Qianli; Liu, Deruo (Journal of Thoracic Disease, 2016)
Background: The aim of this study is to discuss video-assisted thoracic surgery (VATS) sleeve bronchial lobectomy when handling the locally advanced central lung cancer (involving the trachea and/or main bronchus). Methods: A 2.5 cm × 1.0 cm mass was found in the right upper lobe. Bronchoscopy demonstrated the tumor obstructing the right upper lobe bronchus and involved the right main bronchus and bronchus intermedius. Interrupted sutures were chosen for bronchial anastomosis. Bronchial membrane was sutured first, and then circumference end-to-end anastomoses were carried out using 3-0 absorbable sutures. Results: There were no complications and the patient was discharged 8 days postoperatively. Conclusions: The third intercostal space of the anterior axillary line was suggested for right upper lobe bronchial sleeve resection. This incision can reduce the distance and angle between the anastomosis to the incision, and facilitate anastomosis. This approach can also prevent operator from fatigue for keeping one posture for a long time. Clearance of the mediastinal lymph nodes before cutting the bronchus was helpful for exposing the right main bronchus, the upper lobe bronchus and bronchus intermedius satisfied. And this option would avoid pulling bronchial anastomosis during mediastinal lymph nodes clearance. Interrupted suture was safe and effective for VATS bronchial anastomosis.